Penggunaan Media Pembelajaran Augmented Reality Berbantuan Assemblr Edu Untuk Meningkatkan Hasil Belajar Siswa SMA Negeri 5 Kota Ternate - Zulkifli Ahmad; Hasna Ahmad; Zulkarnain Abd. Rahman (Peneliti.net, 2022)
The use of learning media at all levels of education in North Maluku is still quite simple, so an effective alternative learning media is needed in presenting learning so that material that is still abstract can become more concrete, as well as provide a learning experience for students. Given the importance of using instructional media in teaching strategies, this study aims to obtain data on the feasibility and responses of students in using augmented reality learning media. The method used in this study is a quasi-experimental (quasi-experimental). This type of research is qualitative by designing or creating 3D models using the assembler studio, making AR books on the animalia concept, as well as collecting student learning outcomes data using pretest and posttest questions, media effectiveness testing, and material testing using questionnaires that are validated by expert validation, teachers, and students. The results show that the prototype for making AR learning media can be used on Android smartphones and PCs/laptops, and the operation is easy and can be used by various ages and educational backgrounds. Augmented reality learning media developed has a high effectiveness value, and students feel happy in using it, so it can be used in biology learning. The learning outcomes of class X students of SMA Negeri 5 Ternate City on the concept of animalia as measured by the N-Gain test are 4.2 or 1.0% and are categorized as high. The conclusion of the researcher is that the use of augmented reality learning media can be used as a learning medium to improve student learning outcomes.